A Guide to Extract Spinal Cord for Translational Stem Cell Biology Research: Comparative Analysis of Adult Human, Porcine, and Rodent Spinal Cord Stem Cells - Galuta, Ahmad; Sandarage, Ryan; Ghinda, Diana; Auriat, Angela M.; Chen, Suzan; Kwan, Jason C. S.; Tsai, Eve C. (Frontiers in Neuroscience, 2020)
Improving the clinical translation of animal-based neural stem/progenitor cell (NSPC) therapies to humans requires an understanding of intrinsic human and animal cell characteristics. We report a novel in vitro method to assess spinal cord NSPCs from a small (rat) and large (pig) animal model in comparison to human NSPCs. To extract live adult human, pig, and rat spinal cord tissue, we illustrate a strategy using an anterior or posterior approach that was simulated in a pig model. The initial expansion of primary NSPCs is carried out using the neurosphere assay followed by a pharmacological treatment phase during which NSPCs derived from humans, pigs, and rats are assessed in parallel using the same defined parameters. Using this model, NSPCs from all species demonstrated multi-lineage differentiation and self-renewal. Importantly, these methods provide conditions to enable the direct comparison of species-dependent cell behavior in response to specific exogenous signals.